2022
DOI: 10.1186/s13052-022-01235-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidental pineal gland cyst in girls with early onset of puberty

Abstract: Background The causes of an early onset of puberty are still not clearly defined and may vary from subject to subject. In girls, even if 90% of early puberty is idiopathic, magnetic resonance imaging (MRI) of the brain is performed to exclude secondary causes of precocious puberty, in particular pathological lesions as hypothalamic tumours (hamartoma). In some cases, other intracranial lesions are considered as incidental findings. Aim of the study is evaluating the prevalence of abnormal intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It is generally believed that the higher the above indicators are, the faster the pubertal development process is (18). It has been reported that CPP may be related to pineal cysts (9), but some studies have reached the opposite conclusion, suggesting that pineal cysts are an occasional phenomenon in girls with CPP (11). In this study, CPPdiagnosed girls with pineal cysts meeting the study criteria were defined as the cyst group, and CPP-diagnosed girls without cysts were defined as the non-cyst group by 1:1 matching according to age and BMI.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…It is generally believed that the higher the above indicators are, the faster the pubertal development process is (18). It has been reported that CPP may be related to pineal cysts (9), but some studies have reached the opposite conclusion, suggesting that pineal cysts are an occasional phenomenon in girls with CPP (11). In this study, CPPdiagnosed girls with pineal cysts meeting the study criteria were defined as the cyst group, and CPP-diagnosed girls without cysts were defined as the non-cyst group by 1:1 matching according to age and BMI.…”
Section: Discussionmentioning
confidence: 93%
“…In some cases, ataxia, motor and sensory disorders, mood disorders, epilepsy, circadian rhythm disorders, CPP, and secondary Parkinson's disease have been reported (20). Symptomatic cysts range in size from 7 to 45 mm, whereas asymptomatic cysts are usually <10 mm in diameter (11). According to the grouping criteria in previous literature (13), the girls were divided into three groups according to cyst size: ≤5 mm, 5.1-9.9 mm, and ≥10 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI in girls aged 6-8 years is still debated because the incidence of cranial abnormalities in this age group is minimal (21)(22)(23)(24)(25)(26). The most prevalent CNS lesions are hypothalamic hamartomas in the tuber cinereum, which are typically asymptomatic (27,28). In a study in Taiwan on 251 girls with CPP, 190 (75.70%) of the patients had normal MRIs.…”
Section: Discussionmentioning
confidence: 99%